Testemunhos da ditadura: a construção da memória no livro Memórias das mulheres do exílio - Calaça, Vanessa Maria Pereira (2016)
The military dictatorship was a remarkable period in the history of Brazil and there is much debate about which memory is the "true", which memory of this period has to be preserved. All these preservation of relationships and building the dictatorship of memory in bring relevant issues to understand how we as a society, we deal with our past history. This work entitled Testimonies of the Dictatorship: the construction of memory in the book Memories of Exile Women aims to discuss the memories that were produced by brazilian exiled during the military dictatorship. This was a remarkable period that is constantly building by various groups and individuals, and we intend to put these women also in this debate. We use to this research the work Memories Women's exile, which was published in 1980 by Paz e Terra publishing house, where it is present the testimony of 43 different women, but who are in the same situation: exiled. Exile is being away from home, far from their place of origin; and this detachment from Brazil gave these women a time of assessment of their lives, militancy. This documentation as well as the bibliography, was used in order to meet our objective to ascertain that memory of military dictatorship is being built in the accounts of exiled; the meaning assigned by them to that period and issues such as torture, exile, imprisonment, militancy, and trauma.